2006
DOI: 10.1016/j.febslet.2006.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Danggui Buxue Tang – A Chinese herbal decoction activates the phosphorylations of extracellular signal‐regulated kinase and estrogen receptor α in cultured MCF‐7 cells

Abstract: Danggui Buxue Tang (DBT), a Chinese herbal decoction used to treat ailments in women, contains Radix Astragali (Huangqi; RA) and Radix Angelicae Sinensis (Danggui; RAS). The weight ratio of RA to RAS used in DBT must be 5:1 as stipulated as early as AD 1247; however, DBT's mechanism of action has never been described. Here, the estrogenic effects of DBT were investigated by determining the phosphorylations of estrogen receptor a (ERa) and extracellular signal-regulated kinase 1/2 (Erk1/2) in cultured MCF-7 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 26 publications
2
66
0
Order By: Relevance
“…Several line of evidence indicate that this 800-year-old herbal decoction having RA and RAS in a 5:1 ratio possesses the best biological activities in stimulating estrogenic responses (Gao et al, 2007a), immunological responses and bone development ; however, the two herbs have to be boiled together (Gao et al, 2007b;Choi et al, 2009). In good agreement with our previous results, the HIF induction of DBT has a specific requirement of boiling the two herbs together in order to achieve the full biological activity.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Several line of evidence indicate that this 800-year-old herbal decoction having RA and RAS in a 5:1 ratio possesses the best biological activities in stimulating estrogenic responses (Gao et al, 2007a), immunological responses and bone development ; however, the two herbs have to be boiled together (Gao et al, 2007b;Choi et al, 2009). In good agreement with our previous results, the HIF induction of DBT has a specific requirement of boiling the two herbs together in order to achieve the full biological activity.…”
Section: Discussionsupporting
confidence: 77%
“…Pharmacological results indicate that DBT possesses the abilities to promote hematopoietic function, to stimulate cardiovascular circulation, to prevent osteoporosis, to increase anti-oxidation activity, to stimulate immune response and increase insulin sensitivity Gao et al, 2006Gao et al, , 2007aGao et al, ,b, 2008Liu et al, 2009). By determining the chemical and biological properties of DBT, the optimized conditions for herbal extraction have been established (Song et al, 2004), which, interestingly, are in accord HEK293T cells were treated with 1 mg/ml of DBT, RA, RAS, RA + RAS (just mixing the extracts of RA and RAS together in 5:1 ratio but boiled separately) for 48 h. The level of EPO mRNA was revealed by real-time PCR, while 18S rRNA was used as an internal control for normalization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the heat originated from Blood-Xu was described in Neiwaishang Bianhuo Lun by Li Dongyuan in China, 1247 A.D. [33]. 3) From the statistical perspective, there is a collinearity be…”
Section: Acknowledgmentmentioning
confidence: 99%
“…3 Nowadays, DBT is used not only as an efficacious medicine, but also as a common food supplement. Previous studies have demonstrated that DBT has attractive pharmacological activities, including immunoregulation, 4 estrogenic properties, 5 anti-inflammation, 6 stimulation of the T-lymphocytes proliferation, 7 regulating blood lipid and foam cell formation, 8 as well as retarding the progress of diabetic nephropathy. 9 In recent years, metabolism studies of CHMs have attracted significant attention, as they shed additional light on drug efficacy, 10 and enable the screening of bioactive components, 11 the detection of potentially toxic metabolites, 12 the elucidation of herb-drug interactions, 13 and the identification of drug degradation pathways.…”
mentioning
confidence: 99%